Development of Korean CARcinogen EXposure: An Initiative of the Occupational Carcinogen Surveillance System in Korea. Issue 5 (2nd February 2021) - Koh, Dong-Hee; Park, Ju-Hyun; Lee, Sang-Gil; Kim, Hwan-Cheol; Choi, Sangjun; Jung, Hyejung; Kim, Inah; Park, Donguk
Abstract: Objective: To prevent occupational cancers, carcinogen exposure surveillance systems have been developed in many countries. This study aimed to develop a carcinogen exposure database specific to South Korea. Methods: Twenty known human carcinogens were selected for this study. The International Standard Classification of Industry was used for a classification scheme of industries. Three nationwide occupational exposure databases, the Work Environment Measurement Database, the Special Health Examination Database, and the Work Environment Condition Survey, were used to calculate reference exposure prevalence estimates by carcinogen and industry. Then, 37 professional industrial hygienists with at least 19 years of field experience provided their own exposure prevalence estimates, after reviewing the abovementioned reference estimates derived from three data sources. The median value of the experts' estimates was used as the final exposure prevalence. Finally, the number of exposed workers was computed by multiplying the final exposure prevalence by the number of workers extracted from the 2010 national census data by carcinogen and industry. Results: The exposure prevalence and the number of exposed workers were calculated according to 20 carcinogen and 228 minor industrial groups, assuming year 2010 circumstances. The largest population was exposed to welding fumes (326 822 workers), followed by ultraviolet radiation (238 937 workers), ionizing radiation (168 712 workers), and mineral oil mist (146 798 workers). Conclusions: Our results provide critical data on carcinogen exposure for the prevention of occupational cancers.